Gender-Responsive Budget Analysis on Social Protection Programs in Indonesia: A Case Study in Two Districts and A City - Akhmad Misbakhul Hasan; Betta Anugrah; Andi Misbahul Pratiwi (Jurnal Perempuan, 2019)
Presidential Instruction (Inpres) No. 9 of 2000 about Gender Mainstreaming is a mechanism to in National Development has impacts on the planning and implementation of public policy in Indonesia. Public policy becomes an important arena for the struggle to realize gender equality and justice. One of the government’s commitments to this matter can be seen through Gender-Responsive Budgeting (GRB). This study analyses gender responsive budgeting in social protection programs in Indonesia, with case studies in three regions, namely Gunungkidul Regency, North Lombok Regency, and Padang City. Data collection is carried out by in-depth interviews and literature studies, including the Indonesian Budget and Regional Government Budget documents. This study conducted GRB analysis in three regions with three categories of budget expenditure analysis, namely specifically identified gender-based expenditure, equal employment opportunity expenditure, and mainstream budget expenditure. The results of the study show that in several regions there have been gender-responsive specific budget allocations for affirmation programs for women, children, the elderly, and dissability. However, it can be seen that the budget and gender-specific expenditure are still centralized in services that are identical to women's affairs, and not yet mainstreamed in all of the budget allocation.